2006
DOI: 10.1109/tpami.2006.250
|View full text |Cite
|
Sign up to set email alerts
|

Random Multispace Quantization as an Analytic Mechanism for BioHashing of Biometric and Random Identity Inputs

Abstract: Biometric analysis for identity verification is becoming a widespread reality. Such implementations necessitate large-scale capture and storage of biometric data, which raises serious issues in terms of data privacy and (if such data is compromised) identity theft. These problems stem from the essential permanence of biometric data, which (unlike secret passwords or physical tokens) cannot be refreshed or reissued if compromised. Our previously presented biometric-hash framework prescribes the integration of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
179
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 406 publications
(182 citation statements)
references
References 25 publications
2
179
1
Order By: Relevance
“…However, Kong et al showed later in [KCZ * 06] that the recognition performance is degraded in comparison with the unprotected features in the case that projection matrix is stolen and used by impostor. This algorithm is further implemented for palm recognition [CTGN05], face recognition [TwGdCN06] etc.…”
Section: Biometric Template Protectionmentioning
confidence: 99%
“…However, Kong et al showed later in [KCZ * 06] that the recognition performance is degraded in comparison with the unprotected features in the case that projection matrix is stolen and used by impostor. This algorithm is further implemented for palm recognition [CTGN05], face recognition [TwGdCN06] etc.…”
Section: Biometric Template Protectionmentioning
confidence: 99%
“…Randomized dynamic quantization transformation comprises of three steps: (1) Random Projection [5], (2) Dynamic Quantization and (3) Condensation.…”
Section: Randomized Dynamic Quantization Transformationmentioning
confidence: 99%
“…The template protection schemes proposed in literatures can be broadly classified into two categories, feature transformation approach and biometric cryptosystem [2], [3]. The former [4]- [16] has a high degree of freedom for signal processing in the protected domain, compared to the latter [17]- [21]. Feature transform schemes can be further categorized as salting biometric [4]- [8] and noninvertible [9]- [16] transforms.…”
Section: Introductionmentioning
confidence: 99%